Influence of Sustainable Development Guidelines on Dangerous Goods Haulers - Muha, Robert (Promet - Traffic&Transportation, 2012)
In more advanced countries, the sustainable development concept was accepted both by the politicians and the industrial sector as the underlying philosophy for the preparation of development strategies, practically in all fields. This means using the natural resources within the limits of their renewability, and seeing that the resulting emissions have no negative impact on the environment. The development of Environmental Management Systems (EMS) commenced as a response to global environmental issues and as recognition of awareness that sustainable development is prerequisite for keeping the natural system in proper balance. Road transport of dangerous goods is a very complex activity representing a major potential danger to people and environment. For that very reason, the introduction of certain system tools (standardization of operations), that was a step forward to a safer and more effective operation of the carriers of dangerous goods by road was so welcome. However, this policy requires adequate business environment to be prepared, which is based on transparency and smooth operations as an important marketing advantage that has a bearing on every company’s economic performance. KEY WORDS: sustainable development, road transport of dangerous goods, Environmental Management System (EMS), Responsible Care (RC), ISO 140001, Safety and Quality Assessment System (SQAS).